Collaborative Professional Partnership: A Dean and Department Head's Story - Susan M Rugari; James R Pierce (Academic Chairpersons Conference Proceedings, 2016)
Administration has its share of problem-solving. In this presentation, a dean and department head join together to tell the story of the start of their professional relationship, role play their problem-solving process, and identify what they believe are key aspects that make their professional relationship effective.
Keywords: collaborative; professional partnership; active listening; communicate; problem-solving